"I'm Talking About Pain": Sickle cell disease patients with extremely high hospital use. Issue 1 (20th November 2012) - Weisberg, Daniel; Balf‐Soran, Gabriela; Becker, William; Brown, Shan‐Estelle; Sledge, William
Abstract BACKGROUND: A small minority of sickle cell disease patients accounts for the majority of inpatient hospital days. Admitted as often as several times a month, over successive years, this cohort of patients has not been studied in depth despite their disproportionate contribution to inpatient hospital costs in sickle cell disease. OBJECTIVE: To characterize the subjective experience of extremely high hospital use in patients with sickle cell disease, and generate hypotheses about the antecedents and consequences of this phenomenon. DESIGN: Qualitative study involving in‐depth, open‐ended interviews using a standardized interview guide. SETTING: A single urban academic medical center. PARTICIPANTS: Eight individuals, of varying age and gender, identified as the sickle cell disease patients who are among the highest hospital use patients over a 3‐year period. RESULTS: A common narrative emerged from the interview transcripts. Participants were exposed to the hospital environment and intravenous (IV) opioids at a young age, and this exposure was associated with extremely high hospital use in adulthood, evident in descriptions of multiple dimensions of their lives: pain and opioid medication use, interpersonal relationships, and personal development. CONCLUSIONS: Our results suggest a systematic, self‐reinforcing process of isolation from mainstream society, support structures, and caregivers, based on increasing hospitalization, growing dependency on opioid medications, as well as missed developmental milestones. Further study and interventions should be geared towards breaking this spiraling cycle with long‐term strategies in disease management and social integration. Journal of Hospital Medicine 2013. © 2012 Society of Hospital Medicine